2021
DOI: 10.1111/jocd.14038
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐face reshaping using threads with bidirectional convergent barbs: A retrospective study

Abstract: Background: Minimally invasive procedures, such as thread suspension techniques, are a growing trend for facial rejuvenation. However, not enough data are available on the efficacy, outcomes, and morbidity of suture suspension techniques in mid-face reshaping.Aims: Our goal was to assess treatment outcomes and patient satisfaction following mid-face reshaping using threads with bidirectional convergent barbs (Definisse TM free floating threads).Patients/Methods: We performed a retrospective analysis of 60 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…In addition, the surgeons’ satisfaction scores (excellent, very improved, and improved levels) at 6 months after surgery were 2%, 30%, and 64% (totally: 96% for the surgeon), and 2%, 22%, and 72% (totally: 96% for the independent surgeon). Contrary to the study conducted by Santorelli A. et al 15 our study has shown greater satisfaction scores in both patients and surgeons 6 months after facial rejuvenation surgery.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, the surgeons’ satisfaction scores (excellent, very improved, and improved levels) at 6 months after surgery were 2%, 30%, and 64% (totally: 96% for the surgeon), and 2%, 22%, and 72% (totally: 96% for the independent surgeon). Contrary to the study conducted by Santorelli A. et al 15 our study has shown greater satisfaction scores in both patients and surgeons 6 months after facial rejuvenation surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study conducted by Santorelli A. et al 15 most patients, who underwent mid‐face treatment with the suspension thread technique, reported improved and excellent satisfaction based on GAIS score. Based on patients’ improvement assessment, 6 months after the surgery, about 30% reported improved satisfaction, and about 60% of patients reported a much‐improved level of satisfaction.…”
Section: Discussionmentioning
confidence: 98%
“…Thread resorption most likely occurred between 8 and 12 months post-procedure. Based on previous studies and the thread’s composition, neocollagenesis was most likely initiated at 1 month post-implantation [ 18 , 23 , 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used Definisse™ threads, which consist of absorbable p(LA-CL) monofilaments that provide subdermal support or filling, confer elasticity, and prolong thread stability when implanted [ 26 , 28 ]. The double needle threads are convergent bidirectional barbs and are available in 12- or 23-cm versions with 9- or 15-cm 24G straight needles at both thread extremities [ 20 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation